Silver is for secrets - Stolarz, Laurie Faria,frey50 (Woodbury, Minn. : Llewellyn Publications, 2005)
During a summer vacation at the beach with friends, eighteen-year-old hereditary witch Stacey has more nightmares which involve Clara, a new girl with a talent for causing trouble. Stacey's looking forward to relaxing on the beach with the gang and her new boyfriend, but the fun is cut short when the nightmares return. Sensing that Clara, a fifteen-year-old staying down the beach from them, is in deadly trouble, Stacey struggles to discover what's she's hiding before someone gets hurt. After graduation, all Stacey wants to do is relax, hang out with her new boyfriend, Jacob, and enjoy the beach with her friends. But this proves impossible when Stacey's nightmares return, and she senses 15-year-old Clara is in deadly trouble.
Keywords: Witchcraft; Magic; Nightmares; Extrasensory perception; Revenge; Brown, Stacey (Fictitious character); Extrasensory perception; Witchcraft; Occult fiction; Young adult fiction